From parallel trajectories to joint strategy: models of effective integration of military and civilian security expertise - Solovyov , Yevhen (Pressing Problems of Public Administration, 2025)
The article explores models of effective integration of military and civilian security expertise in the context of a prolonged armed conflict. A comparative analysis of institutional mechanisms, methodological approaches, and technological tools for expertise integration in leading NATO countries and states facing asymmetric security threats has been conducted. Three basic models have been identified: the British “adaptive integration”, the Scandinavian “security convergence”, and the Israeli “functional hybridization”. Their institutional, methodological, and technological features are analysed in detail through practical implementation cases. Using the British CENR project, the Finnish “Comprehensive Security Network” program, and the Israeli «AI Vision» system as examples, the specifics of national approaches to integrating expert communities are revealed. Special attention is paid to the impact of artificial intelligence and blockchain technologies on the transformation of expertise integration systems, particularly their potential for expanding collective intelligence capabilities and changing the epistemic structure of expert activities. It is substantiated that these technologies provide a fundamental transition from a hierarchical “intellectual pyramid” to a “distributed cognitive network’ capable of effectively withstanding destructive influences, overcoming epistemic fragmentation, and ensuring high adaptability. The concept of “poly-domain cognitive networks” is analysed as an innovative approach to integrating different types of expertise through shared blockchain infrastructure and AI orchestration. Conceptual foundations of the Ukrainian model of military and civilian expertise integration are proposed, synthesizing the most relevant elements of the studied foreign models, taking into account national specifics and requirements of Euro-Atlantic integration. In the context of expected geopolitical transformation (April 2025), it is proven that the development of such a model creates a unique opportunity for Ukraine’s strategic repositioning from a “security consumer” to an “expertise exporter’ in the new European security architecture, transforming the unique experience of confronting multi-domain aggression into a strategic asset of global significance.